Synergistic Role of Creatine Monohydrate in Mitigating Skeletal Muscle Wasting and Strength Decline during GLP-1 Receptor Agonist Therapy: A Comperhensive Review - Salama, Aladdin; Abdulla, Shafea; Kaminskaya, Anhelina; Ivanchuk, Sofiia; Savchak, Tetiana; Kurek, Aleksandra; Domińczak, Dominika; Górecki, Patryk; Głowacka, Aleksandra; Feretycki, Hubert (Quality in Sport, 2026)
Purpose of Research: The unprecedented clinical adoption of glucagon-like peptide-1 receptor agonists (GLP-1 RAs) and multi-receptor agonists (GIP/GLP-1) for weight management has introduced critical concerns regarding the "quality" of weight loss. Unintended reductions in lean body mass (LBM) often comprise 20–40% of total weight reduction, predisposing patients to sarcopenia and functional decline. This narrative review, using a systematic search strategy, evaluates creatine monohydrate as a potentially beneficial adjunct to GLP-1 therapy for preserving skeletal muscle mass, strength, and health-related quality of life (HRQoL). Research Materials and Methods: A systematic analysis of 60+ peer-reviewed publications (2017–2026) was conducted. Databases included PubMed, Scopus, and the archives of Nicolaus Copernicus University journals (Quality in Sport, Journal of Education, Health and Sport). Basic Results: Clinical trials (STEP, SURMOUNT) confirm that weight loss with incretin mimetics is primarily fat-driven, yet LBM loss remains a significant correlate, particularly in the elderly. Creatine supplementation targets the PCr-ATP energy shuttle and is suggested to activate mTOR signaling and stimulate GLUT-4 translocation independently of insulin. Evidence from the SEMALEAN study and recent D3​-creatine dilution trials suggests that while absolute mass may decline, muscle quality can be preserved through reduced myosteatosis. Both therapies show independent and synergistic potential to improve HRQoL, specifically in physical functioning scores (SF-36). Conclusions: Creatine monohydrate is a safe, cost-effective strategy for high-quality body recomposition. Integrating creatine with resistance training and high-protein intake (1.2–2.0 g/kg/day) represents a robust framework for preventing the "obesity-sarcopenia cycle.”